WordNet: An Electronic Lexical Reference System Based on Theories of Lexical Memory - Miller, George; Fellbaum, Christiane; Kegl, Judy; Miller, Katherine (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1988)
AbstractThis paper describes WordNet, an on-line lexical reference system whose design is based on psycholinguistic theories of human lexical organization and memory.English nouns, verbs, and adjectives are organized into synonym sets, each representing one underlying lexical concept. Synonym sets are then related via three principal conceptual relations: hyponymy, meronymy, and antonymy. Verbs are additionally specified for presupposition relations that hold among them, and for their most common semantic/syntactic frames.By attempting to mirror the organization of the mental lexicon, WordNet strives to serve the linguistically unsophisticated user.